Emergence of two novel viruses in Tibetan pigs with porcine diarrheal disease on the Tibetan plateau of southwest China - Lu, Haohao; Zhang, Min; Yang, Danjiao; Gao, Xue; Feng, Shuo; Pei, Yiwen; Zhang, Zhidong; Zhou, Long (Frontiers in Veterinary Science, 2025)
Porcine diarrheal disease is a major cause of morbidity in Tibetan piglets, however, the causative agents of this disease are rarely reported. Here, the viral diversity associated with porcine diarrheal disease was investigated by analyzing the viral communities from Tibetan pigs on the Tibetan plateau of southwest China. The results revealed that 13 mammalian viruses were identified in a pooled sample. Interestingly, it is the first time that dicistrovirus (DCV) was discovered in pigs and St-Valerien-like virus (StVV) was identified in China. Furthermore, the complete genome sequence of the two strains (DCV/porcine/CHN/SCdc-2024 and StVV/porcine/CHN/SCdc-202402) were obtained. Sequence comparisons and phylogenetic analysis showed that the swine-origin DCV/porcine/CHN/SCdc-2024 strain was classified into the family Dicistroviridae with an unassigned genus, and showed distant relationship with other dicistrovirus strains in established genera, may represent members of a potential new genera within the Dicistroviridae family. Additionally, the novel StVV strain StVV/porcine/CHN/SCdc-202402 was classified into the Valovirus, whereas showed a unique phylogenetic branch compared with other swine-origin StVV strains. Notably, further case–control investigation in the 87 fecal samples using specific RT-PCR found a high DCV-positive detection rate (77.8%) in diarrheic samples with a significant p value (< 0.0001), suggesting the DCV might associated with diarrhea in pigs. Our study reports for the first time the emergence of DCV in pigs and StVV in China, highlighting the need for further research on pathogenicity and transmission in swine hosts.